Natural Occurrence of Major Mycotoxins across the Ginger Value Chain in Nigeria - A. Negedu; D.O. Apeh; I.M. Ogara; C.V. Iyadi; M. Owoloja; U.T. Ibrahim; V.O. Onoja; H.A. Makun (Journal of Food Quality and Hazards Control, 2022)
Background: Ginger which serves as both spices and medicine is susceptible to mycotoxin contamination. This research determined the incidence of major mycotoxins, including Aflatoxins (AFs), Ochratoxin A (OTA), and Fumonisins (FBs) in Nigerian ginger sampled from two main ginger producing states of Nigeria. Methods: Totally, 105 ginger samples were collected including freshly harvested and dried sliced forms. These samples were collected randomly across five stations; farms, aggregating points, processing points, open markets, and storage facilities during the rainy season in June, 2019. The samples were analysed using the Enzyme-Linked Immunosorbent Assay (ELISA) and read by a microplate reader. Results: Incidence of the studied mycotoxins was 80.9, 68.6, and 90.5% for AFs, OTA, and FBs, respectively. While there were low levels of OTA and FBs across the various sample forms. Mean concentrations of AFs were 1.77±1.86 µg/kg (0.00-8.68) and 6.46±6.71 µg/kg (0.00-36.72) in fresh and dried ginger samples, respectively. The results revealed higher levels of AF in storage samples (9.04±10.72 µg/kg) and market samples (4.05±4.41 µg/kg) compared to other samples. However, no significant difference (p>0.05) was observed in the level of contamination across the sample sources. Conclusion: Freshly harvested ginger samples were less contaminated than dried ginger. Among the studied toxins, AF was found as a potential health concern in Nigerian ginger.